The merchant of Venice Shakespeare - Graham, William H. (Director); Waring, James D.; Lewis, Joseph H., 1907-2000.; Tacik, Ann.; Coe, Richard L. (Richard Livingstone), 1914-1995; Shakespeare, William, 1564-1616.; Catholic University of America. Speech and Drama Department; Richard L. Coe Theater Programs Collection (Library of Congress) (1962)
The Catholic University of America Speech and Drama Department, Rev. Gilbert V. Hartke, O.P., head, presents "The Merchant of Venice," by William Shakespeare, directed by William H. Graham, setting and lighting by James D. Waring, costumes designed by Joseph Lewis, costumes executed by Ann Tacik.
University Theatre, December 6-21, 1957.
Title devised by Library staff.
Cast: Robert Strane, Richard Krisher, Clement Feeney Jr., Robert Milli, Justin K. McDonough, James D. Rogers, Mary Jo Randall, Barbara Convey, Robert Jackson, Philip Bosco, Richard Mennen, Jay Ehrlicher, David Sabin, Robert Cessna, Peter Kline, Jane Reilly, Benjamin Wills, Don Sullivan, K.F. Lowry Jr., Robert Taeschner, James Foote.
LC copy has notations by Coe.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1957.